Analisis elektrodinamika relativistik medium linear berotasi pada eksperimen Wilson & Wilson=Analysis of a rotating linear medium relativistic electrodynamics on Wilson ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Electrodynamics fundamental laws in a rotating frame and their applications to Wilson & Wilson experiment have been investigated. Discussion about them will be restricted in a rotating medium with linear response. Applying the principle of general covariance to electrodynamics in a rotating frame yields: creation of induced charge density by rotation, which doesn't violate the conservation of charge